Esophagectomy for very low body weight: a case report and literature review - Zhang, Tianyu; He, Ruyuan; Xiao, Yongguang (Frontiers in Oncology, 2025)
Esophageal cancer (EC) has been widely concerned because of its high incidence, high mortality and high recurrence rate. However, the traditional surgical treatment of EC has poor prognosis and high recurrence rate. Malnutrition is the most common problem in patients with EC before and after surgery, and it has gradually attracted people’s attention because of its important impact on the efficacy, prognosis and treatment of patients with EC. However, EC patients are often accompanied by malnutrition, and their low BMI is often one of the difficulties in the treatment. Here, we report a very low body weight patient with advanced EC treated with neoadjuvant chemoradiotherapy combined with surgery. Our case shows that very low body weight caused by malnutrition should not be a contraindication for surgical treatment, and combined treatment for EC remains to be popularized.